Lake water acidification and temperature have a lagged effect on the population dynamics of Isoëtes echinospora via offspring recruitment. (November 2016) - Čtvrtlíková, Martina; Hejzlar, Josef; Vrba, Jaroslav; Kopáček, Jiří; Nedoma, Jiří; Hekera, Petr; Wade, Andrew J.; Roy, Shovonlal
Highlights: Lake water acidification controls quillwort recruitment success. Acidity and aluminium toxicity threatens plants aged less than one-year. Cumulative temperature in spring and summer controls subsequent plant growth. Annual change in adult plant abundance indicates recovery rate from acidification. Abstract: The aquatic quillwort, Isoëtes echinospora, survived the strong water acidification during 1960s–1990s in Plešné Lake (Bohemian Forest, Central Europe), but failed to reproduce. We studied the relationships between a recent population recovery and an improvement of lake water quality. We used correlation analysis to evaluate lagged seasonal effects of lake water quality on population dynamics during the past decade, and factor analysis to determine the independent factors responsible for population recovery. We also provided a water-quality-based reconstruction of population growth from the beginning of the lake recovery two decades ago, using a partial least squares regression (PLSR) model of population growth. We identified three independent controlling factors: nutrients (nitrate, phosphorus, calcium, potassium, magnesium), stressors (pH, ionic aluminium) and temperature. Of these, nutrient availability did not limit the quillwort growth, but annual mean pH and winter mean concentrations of toxic ionic aluminium influenced population growth through negative effects on sporeling establishment until the age of one year, while cumulative temperature in spring and summer controlled the later plant growth. Thus, water quality in the acidified Plešné Lake mainly controls recruitment success rather than adult survival of Isoëtes echinospora . This study provides the first in situ evidence that the recruitment success, namely the annual increment in the adult quillwort population, indicates the degree of recovery from acidification, however further extensive investigation is required to more accurately quantify, and therefore understand, the relationships between recruitment, water quality and other factors.